Leaders Of Entrepreneurship And Motivation Effect On Employee Satisfaction At PT. Panarub Industry Tangerang - Hamdan, Hamdan (Jurnal Manajemen, 2018)
This study aims to determine the effect of leadership on job satisfaction,Entreuprunersip and motivation of employees at PT. Panarub Industry Tangeranang. This study used a descriptive questionnaire (questionnaire), which were distributed to 77 (seventy-seven) a sample of respondents of this study, the data come from populations that are normally distributed and have the same variance.The method used is descriptive method that aims to elaborate or provide an overview of the properties or characteristics of a particular phenomenon, and methods of verification or causal to analyze the relationships between the other variables or the way the other vaiabel using statistics.Data collection techniques using a questionnaire with Likert scale measurement. Determination of the sample based on the sample is saturated. Test Instrument with the data analysis and hypothesis testing.Based on the research and statistical calculations, it is known that resgresi linear equation Y = 14.885 + 0.614X1+0.053X2, the correlation coefficient R = 0.723, while the coefficient of determination is seen from R Square = 0.522 means that leadership and motivation of independent variables in explaining the dependent variable 52.2% of the remaining 47.8% is influenced by other factors such as work culture, discipline, work environment, etc. are not included in this study. And There is a significant relationship between leadership and motivation on job satisfaction of employees at PT. Panarub Industry Tangerang in the t test, the results obtained t test > t table (4,281> 1,992) it can be concluded that there is a significant difference between leadership entreupreunership (X1) and motivation (X2) on employee job satisfaction (Y) on PT. Panarub Industry Tangerang. Keywords: Leadership Entreupreunership, Motivation and Job Satisfaction